Pengawasan Ombudsman Republik Indonesia pada Penerimaan Peserta Didik Baru (PPDB) Jenjang Sekolah Menengah Atas (SMA) di Kota Bandung - Febrianti, Anita; Fauzi, Lukman Munawar; Kushartono, Toto (Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the supervision carried out by the Ombudsman of the Republic of Indonesia in supervising the Admission of New Students (PPDB) at the Senior High School (SMA) level in Bandung City. The method used in this research is a qualitative descriptive method. The results of this research show that Ombudsman supervision not only functions as an evaluation tool, but also as a driver for changes in the PPDB system at Senior High School Level (SMA) in Bandung City.